2014
DOI: 10.1371/journal.pone.0100903
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mind-Body Therapies on the Immune System: Meta-Analysis

Abstract: ImportancePsychological and health-restorative benefits of mind-body therapies have been investigated, but their impact on the immune system remain less defined.ObjectiveTo conduct the first comprehensive review of available controlled trial evidence to evaluate the effects of mind-body therapies on the immune system, focusing on markers of inflammation and anti-viral related immune responses.MethodsData sources included MEDLINE, CINAHL, SPORTDiscus, and PsycINFO through September 1, 2013. Randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
174
2
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(197 citation statements)
references
References 98 publications
5
174
2
7
Order By: Relevance
“…Indeed, mind-body interventions that target stress-response pathways also influence inflammatory dynamics. Our meta-analyses found that a variety of different approaches including Tai chi, Yoga, and meditation, reduce circulating levels of CRP, for example (Morgan et al, 2014). Building on this work, genomics-based methods have been recently used to assess inflammation.…”
Section: Behavioral Treatment Of Sleep Disturbance: Impact On Inflammmentioning
confidence: 77%
“…Indeed, mind-body interventions that target stress-response pathways also influence inflammatory dynamics. Our meta-analyses found that a variety of different approaches including Tai chi, Yoga, and meditation, reduce circulating levels of CRP, for example (Morgan et al, 2014). Building on this work, genomics-based methods have been recently used to assess inflammation.…”
Section: Behavioral Treatment Of Sleep Disturbance: Impact On Inflammmentioning
confidence: 77%
“…Including integrative health care modalities in nursing curriculum 6 shown to be effective in improving heart rate variability and decreasing anxiety (Morgan, Irwin, Chung, & Wang, 2014). In keeping with this evidence three IHC modalities were selected by the holistic nurse mentor, Foot Reflexology, Breathing for Sleep and Lavender Aromatherapy.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Studies have shown that yoga, intense physical exercise, meditation, acupuncture, dark chocolate consumption, singing, dancing improves the psychological status by reducing stress, increases social bonding by oxytocin release, physical status, increase immune cells and their activity such as macrophages, NK cells, T and B lymphocytes by beta endorphins release in patients with cancers, lead to lowering inflammation, cellular function enhancement, improves health outcome, later results in better prognosis [1,[16][17][18][19][20][21][22][23][24]27,29,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Clinical Studies Of Beta Endorphins On Different Types Of Camentioning
confidence: 99%